Factors affecting total and "respirable" dose delivered by a salbutamol metered dose inhaler. Issue 7 (July 1995) - Everard, M L; Devadason, S G; Summers, Q A; Le Souëf, P N
Abstract : BACKGROUND--Many factors contribute to the high variability of doses delivered to the lungs of patients using metered dose inhalers (MDIs). Relatively little attention has been paid to the contribution to this variability of the way in which the MDI is handled before the inhalation manoeuvre. Instruction leaflets often recommend procedures at odds with those used for in vitro testing of the device. The standard protocol for in vitro assessment of salbutamol MDIs involves shaking the MDI vigorously for 30 seconds and wasting the first two actuations. Subsequent actuations are introduced into the testing device at five second intervals. Patient instructions do not include a recommendation to waste the first two actuations and recommend a delay of one minute between actuations. A series of experiments was performed to determine whether such differences might be important. METHODS--The total and "respirable" doses delivered by a salbutamol MDI (Ventolin, Allen & Hanburys) under various conditions were assessed with a multistage liquid impinger. The quantity of drug deposited on each stage was measured by an ultraviolet spectrophotometric method. The effect on the delivered dose of not shaking the canister, not wasting the first two doses, waiting 30 seconds between actuations, and using multiple rapid actuations was assessed by comparing the results with those obtained using the standard in vitro testing protocol. RESULTS--Compared with a standard protocol, it was found that not shaking the MDI before use reduced the total and "respirable" dose by 25.5% and 35.7%, respectively. The dose delivered when actuating the MDI at 30 second intervals was no different from that when intervals was no different from that when intervals of five seconds were used. Two actuations separated by one second had no effect on the total dose but reduced the "respirable" dose by 15.8%, while four rapid actuations reduced the total and "respirable" doses by 8.2% and 18.2%, respectively. Storing the MDI stem down reduced the total and "respirable" dose delivered in the first actuation by 25.0% and 23.3% despite shaking the MDI before use. CONCLUSIONS--MDIs containing drug in suspension must be shaken before use to resuspend the drug contained in the MDI, but shaking does not alter the composition of the suspension in the metering chamber and hence the dose in the first actuation remains low. Very rapid actuations can reduce the dose delivered per actuation, but salbutamol MDIs can be actuated immediately after a 10 second breath holding pause without affecting the dose delivered.